2019
DOI: 10.1063/1.5085643
|View full text |Cite
|
Sign up to set email alerts
|

Verification and mitigation of ion migration in perovskite solar cells

Abstract: Metal halide perovskite materials have shown versatile functionality for a variety of optoelectronic devices. Remarkable progress in device performance has been achieved for last few years. Their high performance in combination with low production cost puts the perovskite optoelectronics under serious consideration for possible commercialization. A fundamental question that remains unanswered is whether these materials can sustain their optoelectronic properties during harsh and prolonged operational condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
163
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(178 citation statements)
references
References 94 publications
10
163
0
Order By: Relevance
“…After only 3 min, we see a small amount of UC PL recovery and after 35 min in the dark a larger amount of recovery. This indicates that the interfacial charge accumulation occurs only very slowly and requires several hours to recover, consistent with the timescale of cation migration in the perovskite film 37.…”
supporting
confidence: 66%
“…After only 3 min, we see a small amount of UC PL recovery and after 35 min in the dark a larger amount of recovery. This indicates that the interfacial charge accumulation occurs only very slowly and requires several hours to recover, consistent with the timescale of cation migration in the perovskite film 37.…”
supporting
confidence: 66%
“…Overviews of important studies identifying and controlling the ion migration process can be consulted in reviews. 54,55 For example, the ultrasoft and polarisable lattice of the a-FAPbI 3 system produces polarons (through electron-phonon coupling) with a coherence length similar to the 1.4 nm described above, without any connection to the material being in a mesoporous matrix or not. 56 DFT is currently the most accepted technique for targeting and isolating the origin of point defects.…”
Section: Intrinsic Point Defects and Defect Tolerancementioning
confidence: 95%
“…[9][10][11][12][13] More importantly, due to the ionic nature of perovskite materials, and the low formation [14] and migration activation energies [15,16] of the ionic species, a large number of the ions are mobile in the presence of a potential gradient, and this has been shown to have significant negative repercussions on the long-term operational stability of PSCs since mobile ions can migrate toward and into the adjacent contact layers to rupture the perovskite lattice and degrade the charge extracting/transporting functionality of the contacting layers. [15,[17][18][19] Various strategies have been reported to enhance the stability of PSCs. Particularly, compositional engineering involves substituting or replacing the "A" site cation or "X" site anion in the APbX 3 (X is one of or a mixed of I − , Cl − or Br − ) perovskite lattice.…”
Section: Doi: 101002/adma201906995mentioning
confidence: 99%
“…[52] Upon the exclusion of external environmental factors such as moisture and oxygen by proper encapsulation or an inert atmosphere, the instability of PSCs under illumination should be largely due to the migration of mobile ions due to the light-induced potential gradient to degrade the perovskite and adjacent contact layers. [17,19,[52][53][54] For instance, migrating I − can undergo an irreversible redox reaction to reduce spiro-OMeTAD + to its neutral state to degrade its p-doping character and thus degrade its hole conductivity and deteriorate the device performance. [53] It was also shown that I − migrating out of the perovskite layer can deplete I − from the perovskite layer to rupture its stoichiometry and lattice structure, in addition to reacting with Ag to form AgI to corrode the metal electrode.…”
Section: Doi: 101002/adma201906995mentioning
confidence: 99%